A Systematic Literature Review on the Role of Academic Libraries in Supporting Digital Learning Through ICT Integration - Rismadani; Zulnadila; M. Nur Rahmat Achdar HT; Anugrawati; M. Ardiansyah WH (Jurnal Pendidikan Teknologi, 2026)
The rapid advancement of Information and Communication Technology (ICT) has significantly transformed the role of academic libraries in higher education, particularly in supporting digital learning. Academic libraries are no longer limited to managing printed collections but have evolved into digital learning hubs that facilitate access to information resources, enhance information literacy, and support research and teaching activities through technology integration. However, previous studies on this topic remain fragmented and often focus on specific aspects, making it difficult to obtain a comprehensive understanding of the evolving role of academic libraries. Therefore, this study aims to synthesize existing research on the role of academic libraries in supporting digital learning through ICT integration. This study employed a Systematic Literature Review (SLR) following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A total of 38 records were identified from several academic databases, and after the screening and eligibility processes, 10 peer-reviewed journal articles published between 2020 and 2025 were included in the final analysis. The findings revealed five major themes: (1) ICT integration as the foundation of academic library transformation, (2) digital library services supporting digital learning, (3) academic libraries as centers for information literacy and research support, (4) challenges in ICT implementation, and (5) the emergence of Artificial Intelligence (AI) and smart library systems. The review concludes that ICT integration has fundamentally transformed academic libraries into strategic partners in digital learning and higher education innovation. The findings provide valuable insights for librarians, educators, higher education institutions, and policymakers in developing sustainable and technology-enhanced library services.